2008
DOI: 10.1111/j.1753-4887.2005.tb00158.x
|View full text |Cite
|
Sign up to set email alerts
|

Weekly Iron-Folic Acid Supplements to Prevent Anemia among Cambodian Women in Three Settings: Process and Outcomes of Social Marketing and Community Mobilization

Abstract: and the Cambodian Weekly Iron-Folic Acid Program Team Social marketing and community mobilization approaches were applied in a pilot program to introduce weekly iron-folic acid supplementation to prevent anemia in Cambodian women of reproductive age. The program was implemented in three very different environments: secondary school girls, women working in garment factories in the vicinity of Phnom Penh, and women in rural villages. Each population provided its own challenges and obstacles. However, all three g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…In a study in Indonesia that assessed determinants of community-based periodic vitamin A supplementation programmes in children also indicated that coverage was higher in villages which were economically less developed (25) . In that study it was shown that the highest performance was achieved by village distributors who were less educated and represented the local status quo rather than more upwardly mobile, highly educated ones (24) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study in Indonesia that assessed determinants of community-based periodic vitamin A supplementation programmes in children also indicated that coverage was higher in villages which were economically less developed (25) . In that study it was shown that the highest performance was achieved by village distributors who were less educated and represented the local status quo rather than more upwardly mobile, highly educated ones (24) .…”
Section: Discussionmentioning
confidence: 99%
“…In that study it was shown that the highest performance was achieved by village distributors who were less educated and represented the local status quo rather than more upwardly mobile, highly educated ones (24) . However, a weekly Fe-folic acid supplement delivered with social marketing to pregnant women in Cambodia found that compliance to the supplement was higher among women of higher socio-economic status (25) and an Fe supplementation study in infants in southern Fig. 1 Reasons reported by 1520 women for not taking tablets regularly among those who perceived not taking them regularly: , forgot to take; , was at parents' home; , due to side-effects; , did not like tablets; , would cause harm; , did not take around delivery; , taking other medicines; , other.…”
Section: Discussionmentioning
confidence: 99%
“…Community-based distribution of iron-folic acid supplementation is a valuable platform to increase awareness and knowledge of anaemia and iron-folic acid supplementation Seven studies reported on increased knowledge and coverage of IFA supplementation through provision of messages and counselling on anaemia and IFA supplementation through community-based channels (17)(18)(19)(20)(21)(22)(23) . A study from Iran found that CHW provided counselling on the importance of taking IFA supplements for reducing anaemia.…”
Section: Strengths Of Community-based Distribution Of Ironfolic Acid mentioning
confidence: 99%
“…• Increased awareness of iron-deficiency anaemia, its causes and effects, and the importance of weekly IFA supplementation Kanal et al (18) 2005 Cambodia Pilot programme of social marketing and community mobilization in secondary-school girls, women working in urban garment factories and women in rural villages. Supplements were distributed or sold by volunteer school-based peer educators, garment factory team leaders and rural peer educators, respectively…”
Section: Strengths Of Community-based Distribution Of Ironfolic Acid mentioning
confidence: 99%
“…For these reasons Honduras would benefit more from the implementation of a cost-effective preconceptional folic acid supplementation programme that would reach the poor urban and rural high-risk populations. Recently, the regional office of the WHO in South Asia (Philippines, Cambodia and Vietnam) published results on community trials assessing the effectiveness of micronutrient supplementation to the population with a pill containing both Fe and folic acid (37)(38)(39)(40)(41)(42) . The strategy tailored the supplementation intervention and market strategy to each country's culture and values.…”
Section: Discussionmentioning
confidence: 99%